Результат упрощения выражения (3tga + 6ctga) · sin2α -12cos^2α имеет вид?помогите плиз

Результат упрощения выражения (3tga + 6ctga) · sin2α -12cos^2α имеет вид? помогите плиз
Гость
Ответ(ы) на вопрос:
Гость
[latex](3tga+6ctga)*sin(2a)-12cos^{2}a=(\frac{3sina}{cosa}+\frac{6cosa}{sina})*sin(2a)-12cos^{2}a=[/latex][latex]=\frac{3sina*2sina*cosa}{cosa}+\frac{6cosa*2sina*cosa}{sina}-12cos^{2}a=[/latex][latex]=3sina*2sina+6cosa*2*cosa-12cos^{2}a=6sin^{2}a+12cos^{2}a-12cos^{2}a[/latex][latex]=6sin^{2}a[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы